Wildfire smoke in the Siberian Arctic in summer: source characterization and plume evolution from airborne measurements - Paris, J.-D.; Stohl, A.; Nédélec, P.; Arshinov, M.Yu.; Panchenko, M.V.; Shmargunov, V.P.; Law, Kathy S.; Belan, B.D.; Ciais, P. (Atmospheric Chemistry and Physics, 2009)
International audience We present airborne measurements of carbon dioxide (CO2), carbon monoxide (CO), ozone (O3), equivalent black carbon (EBC) and ultra fine particles over North-Eastern Siberia in July 2008 performed during the YAK-AEROSIB/POLARCAT experiment. During a "golden day" (11 July 2008) a number of biomass burning plumes were encountered with CO concentration enhancements of up to 500 ppb relative to a background of 90 ppb. Number concentrations of aerosols in the size range 3.5–200 nm peaked at 4000 cm−3 and the EBC content reached 1.4 μg m−3. These high concentrations were caused by forest fires in the vicinity of the landing airport in Yakutsk where during the descent measurements in fresh smoke could be made. We estimate a combustion efficiency of 90±3% based on CO and CO2 measurements. The emission factor of CO emitted was 59.6±15.2 g CO per kilogram of dry matter burned, suggesting an increase in the average northern hemispheric CO concentration of 3.0–7.2 ppb per million hectares of Siberian forest burned. For BC, we estimate an emission factor of 0.52±0.07 g BC kg−1, comparable to values reported in the literature. The emission ratio of ultra-fine particles (3.5–200 nm) was 26 cm−3 (ppb CO)−1, consistent with other airborne studies.